Analysis of Junior Secondary Science Curriculum with Respect to Education for Sustainable Development (ESD) in Srilanka - Nithlavarnan, A.; Sinnathambi, K.; Gunawardana, G.I.C. (Royal Asiatic Society of Srilanka, 2016)
Scientific literacy, knowledge and Skills in the society are essential for understanding and addressing the issues for achieving sustainable development. A quality science education is central to building a scientifically literate population. Incorporating of ESD into curriculum is a key aspect and level of intervention, identifying learning outcomes, and training of teaching methods and assessments are some vital areas to consider. This study analyses the existing junior secondary science curriculum with respect to sustainable development it identified the problems in curriculum contents and its implementation of junior secondary Science curriculum at school level. The study followed a mixed method approach. Both qualitative and quantitative methods have been used for data collection and data analysis .the study used multiple methods of inquiry, such as literature review, document perusal including content analysis of curriculum materials and surveys for Science teachers. The survey study sample consisted 136 science teachers from 60 secondary school in Northern Province of Srilanka. School were selected by using stratified random sampling method. Data was collected from Science teachers by using a questionnaire as a data collection tool. Descriptive data analysis method was used. A properly planned science education policy hasn’t been worked out to date. Existing science curriculum has been prepared based on National Educational Goals and basic competencies. These are more related to ESD. Already objective for Grade 6 to 11 are also directly linked with ESD. Already existing curriculum includes some competencies related to ESD within the themes of observing the environment, organisms and life process, matter, earth and space energy, force and work. The Science curriculum incorporates environmental aspects to a greater extent than socio economic and cultural aspects. Likewise cognitive contents are more emphasized than the Skill and Value contents In general science curriculum. Several problem were identified in the existing science curriculum contents and its implementation. Science teachers also gave suggestions for improving junior secondary science curriculum pertaining to sustainable development. Through solving these problems and enriching the science curriculum with ESD aspects, Srilanka is expected to move towards sustainable development.
Keywords: Education for Sustainable Development; Science Curriculum; Junior Secondary